2016
DOI: 10.1038/mp.2015.192
|View full text |Cite|
|
Sign up to set email alerts
|

Brain iron accumulation affects myelin-related molecular systems implicated in a rare neurogenetic disease family with neuropsychiatric features

Abstract: The ‘neurodegeneration with brain iron accumulation' (NBIA) disease family entails movement or cognitive impairment, often with psychiatric features. To understand how iron loading affects the brain, we studied mice with disruption of two iron regulatory genes, hemochromatosis (Hfe) and transferrin receptor 2 (Tfr2). Inductively coupled plasma atomic emission spectroscopy demonstrated increased iron in the Hfe−/− × Tfr2mut brain (P=0.002, n ≥5/group), primarily localized by Perls' staining to myelinated struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 72 publications
(105 reference statements)
3
51
1
Order By: Relevance
“…Similarly, some hemochromatosis patients display schizophrenia-like or bipolar symptoms (76,77). In rodents, Heidari et al (78) found that Hfe 2/2 xTfr2 mut mice with brain iron overload are hyperactive. However, mixed results also exist; iron overload is associated with hypoactivity, increased anxiety, or no change in emotional behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some hemochromatosis patients display schizophrenia-like or bipolar symptoms (76,77). In rodents, Heidari et al (78) found that Hfe 2/2 xTfr2 mut mice with brain iron overload are hyperactive. However, mixed results also exist; iron overload is associated with hypoactivity, increased anxiety, or no change in emotional behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These pathologies together can generate mixed-signal and may lead to such discrepancies as observed between R3 and R1, R2 (76, 77). In areas with increased GFAP activity the magnetic susceptibility signature of iron and myelin changes and it is difficult to isolate myelin from iron during the pathological cascade groups (78,79). Also, in white matter, iron deposition has been shownto be minimal compared to the known demyelination process (36).…”
Section: Axonal Damage and Myelin Fragmentationmentioning
confidence: 99%
“…On the other hand, excessive iron concentration in macrophages may promote a pro-inflammatory M1 activation state and facilitate inflammation [167]. In an animal model of cerebral iron overload, expression of several NBIA-related proteins involved in phospholipid and myelin metabolism was decreased suggesting that iron accumulation may influence myelin synthesis and maintenance [168]. Several studies showed that chelators ameliorate experimental autoimmune encephalomyelitis which is an animal model of MS.…”
Section: Multiple Sclerosismentioning
confidence: 99%